On Minty variational principle for nonsmooth vector optimization problems with generalized approximate convexity. (3rd August 2018) - Gupta, Pooja; Mishra, S. K.
Abstract: In this paper, we consider a nonsmooth vector optimization problem involving locally Lipschitz generalized approximate convex functions and find some relations between approximate convexity and generalized approximate convexity. We establish relationships between vector variational inequalities and nonsmooth vector optimization problem using the generalized approximate convexity as a tool.